2013
DOI: 10.1016/j.febslet.2013.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the recognition sequence and target proteins for DJ‐1 protease

Abstract: a b s t r a c t DJ-1, the product of familial Parkinson's disease gene and an oncogene, is a cysteine protease which plays a role in anti-oxidative stress reaction. In this study, we identified the recognition sequence for DJ-1 protease by using recombinant DJ-1 and a peptide library. Protease activity of DJ-1 lacking Cterminal a-helix (DJ-1DH9) was stronger than that of full-sized DJ-1, and the most susceptible sequence digested by DJ-1DH9 was valine-lysine-valine-alanine (VKVA) under the optimal conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
(49 reference statements)
1
16
1
Order By: Relevance
“…It has been also shown that Cterminal truncated forms of DJ-1 have increased protease activity, while wild-type DJ-1 does not. This may be in line with our observations in this study, suggesting a critical role in intermonomer interactions between the C-terminal and His126 region [57]. On the basis of the analysis of DJ-1 crystal structures, Wilson et al suggested that the formation of over-oxidized Cys106 is sterically disfavored by the surrounding residues, particularly the Cβ atom of His126 [58].…”
Section: Higher Thermal Stability Of Oxidized and Over-oxidized Dj-1 supporting
confidence: 92%
“…It has been also shown that Cterminal truncated forms of DJ-1 have increased protease activity, while wild-type DJ-1 does not. This may be in line with our observations in this study, suggesting a critical role in intermonomer interactions between the C-terminal and His126 region [57]. On the basis of the analysis of DJ-1 crystal structures, Wilson et al suggested that the formation of over-oxidized Cys106 is sterically disfavored by the surrounding residues, particularly the Cβ atom of His126 [58].…”
Section: Higher Thermal Stability Of Oxidized and Over-oxidized Dj-1 supporting
confidence: 92%
“…6), indicating that DJ-1 is able to activate c-Raf without other factors under these conditions. Although DJ-1 has several enzymatic activities, including protease (37)(38)(39)(40) and glyoxalase activities (41)(42)(43)(44), there is no report showing that DJ-1 is a protein kinase and that DJ-1 has a structural motif for kinase (3)(4)(5). These results therefore suggest that DJ-1 enhances self-phosphorylation activity of c-Raf without a role as kinase.…”
Section: Discussionmentioning
confidence: 79%
“…Several studies have suggested the protease activity of DJ-1; however, this protease activity is very low. (30) Both the cleavage of the C-terminal helix under oxidative stress and the increase in the protease activity of the C-terminal helix deletion mutant have been reported. (30) However, the physiological role of DJ-1 as a cysteine protease is still under debate.…”
Section: Protein Characterization Of Dj-1mentioning
confidence: 99%
“…(30) Both the cleavage of the C-terminal helix under oxidative stress and the increase in the protease activity of the C-terminal helix deletion mutant have been reported. (30) However, the physiological role of DJ-1 as a cysteine protease is still under debate. In addition, the tertiary structure of DJ-1 was similar to that of E. coli heat shock protein HSP31, a structural homolog of PH1704 protease.…”
Section: Protein Characterization Of Dj-1mentioning
confidence: 99%